ANALYSIS OF FEED PREFERENCES DROP IN TIMOR DEER (Cervus timorensis) IN DEER CAPTURE LAMPUNG UNIVERSITY - Seftilia Sari; Bainah Sari Dewi; Rusita Rusita; Sugeng P. Harianto (University of Lampung, 2022)
.The Timor deer (Cervus timorensis) is a protected wildlife. The population of the Timor deer is decreasing, so captivity is a way to save wildlife. Deer breeding at the University of Lampung is one of the ex-situ conservation efforts for the Timor deer (Cervus timorensis) in its natural habitat in an endangered condition. Timor deer drop-in feed in captivity is provided for daily feed needs. The purpose of this study was to determine the types of drop-in feed for the Timor deer, determine the feed preferences of the Timor deer and determine the feeding behavior. The research location is a deer captive at the University of Lampung in the province of Lampung. The method used in this research is scan sampling. The analysis is carried out by descriptive analysis through data analysis. The research was carried out for three months, namely July 2021 on the 1st, 4th, 8th and 12th, August 2021 on the 1st, 4th, 8th, and 12th and September on the 1st, 4th, 8th and 12th. The results of this study are There are 4 types of feed provided by the deer management at the University of Lampung, namely elephant grass (Pennisetum purpureum), Timunan grass (Leptochloa fusca), teki grass (Cyperus rotundus) and insulin grass (Chamaecostus cuspidatus). The feed preferences of deer at the University of Lampung deer are grass plant (Chamaecostus cuspidatus) with an average consumption of 55.83%, elephant grass (Pennisetum purpureum) is 18.75%, teki grass (Cyperus rotundus) 16.83%, while the The least feed was Timunan Grass (Leptochloa fusca) with an average of 9.13%. The eating behavior of the male deer was the highest, the Timor deer, Sugeng, 30.08% and the lowest, the Timor deer, Asep, 28.17%, while the female deer was the highest at East Timor deer, Atik 32.00% and the lowest was Timor deer, Dewi 28.62%.